An experimental study examining the impact of humor therapy on depression level and overall quality of life in the elderly population - Sushil Kumar Gayakwad; Dr. Devraj Singh Chouhan (The Bioscan, 2025)
Background Several studies have demonstrated that humor therapy plays a vital role in maintaining balance across the biological, psychological, social, and cultural dimensions of life among older adults. Purposeful laughter promotes positive emotions, enhances happiness, and contributes to overall well-being. Furthermore, empirical evidence suggests that humor therapy can significantly reduce symptoms of depression and consequently improve the quality of life in the elderly population. Methodology A true experimental two-group pretest–post-test design was adopted for the study, conducted in selected community areas and old-age homes of the Sabarkantha district, Gujarat. A total of 200 elderly individuals (aged 60 years and above) exhibiting symptoms of depression were recruited through purposive sampling and randomly assigned to experimental and control groups, each comprising 100 participants. The experimental group received humor therapy sessions three times per week for a duration of three weeks, while the control group continued to receive standard care. Data were collected using a validated tool developed with expert input (Cronbach’s α = 0.84), along with standardized instruments such as the Geriatric Depression Scale (GDS) and the World Health Organization Quality of Life (WHOQOL) scale. Statistical analysis was performed using both descriptive and inferential methods, including paired and unpaired t-tests and Chi-square tests. Ethical approval for the study was obtained from the Medistar Hospital Ethics Committee (Approval No. P.NO/EC/04/2024). Results Post-intervention, the experimental group demonstrated a significant reduction in depression scores, decreasing from 18.76 ± 2.89 to 10.9 ± 1.78 (p < 0.05), whereas the control group showed only a marginal change. Notably, 59% of participants in the experimental group achieved normal depression scores following the intervention. In addition, the experimental group reported significantly higher quality of life scores (55.96 ± 5.93) compared to the control group (42.40 ± 6.28; p < 0.05). Participants in the experimental group also exhibited a more favorable attitude toward humor therapy, reflected in greater improvements in both quality of life and depression reduction. Furthermore, depression levels were found to be significantly associated with demographic variables such as age, sex, marital status, occupation, income, religion, and source of information. Conclusion Humor therapy was found to reduce depression levels, enhance positive attitudes toward the use of humor, and improve overall quality of life experiences among older adults. These findings suggest that humor therapy should be integrated into routine care for the elderly to promote psychological well-being, strengthen coping abilities for managing depressive situations, and ultimately enhance their quality of life. KEYWORDS: Humor therapy, depression, elderly people, quality of life, old age home, community areas.